Comparison of Time Domain and Spectral Domain Optical Coherence Tomography in Measurement of Macular Thickness in Macular Edema Secondary to Diabetic Retinopathy and Retinal Vein Occlusion. (24th July 2012) - Hatef, Elham; Khwaja, Afsheen; Rentiya, Zubir; Ibrahim, Mohamed; Shulman, Matthew; Turkcuoglu, Peykan; Sepah, Yasir; Wang, Jianmin; Channa, Roomasa; Bittencourt, Millena; Akhtar, Abeer; Heo, Jangwon; et al.
Abstract : Purpose . To evaluate macular thickness, agreement, and intraclass repeatability in three optical coherence tomography (OCT) devices: the time domain (TD) Stratus OCT and two spectral domain (SD) OCTs, Spectralis and Cirrus SD-OCT, in eyes with macular edema secondary to diabetic retinopathy (DR) and retinal vein occlusion (VO). Methods . In a prospective observational study at a university-based retina practice, retinal thickness tomography was performed simultaneously for fifty-eight patients (91 eyes) with DR and VO employing a time domain and two spectral domain OCTs. Agreement in macular measurements was assessed by constructing Bland-Altman plots. Intraclass repeatability was assessed by intraclass correlation coefficients (ICCs). Results . Based on the Bland-Altman plots for central macular thickness, there was low agreement between the measurements of Cirrus SD-OCT and Stratus OCT, Spectralis OCT and Stratus OCT, as well as Spectralis OCT and Cirrus SD-OCT among DR and RVO patients. All three devices demonstrated high intraclass repeatability, with ICC of 98% for Stratus OCT, 97% for Cirrus SD-OCT, and 100% for Spectralis OCT among DR patients. The ICC was 97% for Stratus OCT, 79% for Cirrus SD-OCT, and 91% for Spectralis OCT among RVO patients. Conclusion . There are low agreements among interdevice measurements. However, intraclass repeatability is high in both TD and SD-OCT devices.